Influence of Men's Personality and Social Support on Treatment Decision-Making for Localized Prostate Cancer. (12th July 2017) - Reamer, Elyse; Yang, Felix; Holmes-Rovner, Margaret; Liu, Joe; Xu, Jinping
Abstract : Background . Optimal treatment for localized prostate cancer (LPC) is controversial. We assessed the effects of personality, specialists seen, and involvement of spouse, family, or friends on treatment decision/decision-making qualities. Methods . We surveyed a population-based sample of men ≤ 75 years with newly diagnosed LPC about treatment choice, reasons for the choice, decision-making difficulty, satisfaction, and regret. Results . Of 160 men (71 black, 89 white), with a mean age of 61 (±7.3) years, 59% chose surgery, 31% chose radiation, and 10% chose active surveillance (AS)/watchful waiting (WW). Adjusting for age, race, comorbidity, tumor risk level, and treatment status, men who consulted friends during decision-making were more likely to choose curative treatment (radiation or surgery) than WW/AS (OR = 11.1, p < 0.01 ; 8.7, p < 0.01 ). Men who saw a radiation oncologist in addition to a urologist were more likely to choose radiation than surgery (OR = 6.0, p = 0.04 ). Men who consulted family or friends (OR = 2.6, p < 0.01 ; 3.7, p < 0.01 ) experienced greater decision-making difficulty. No personality traits (pessimism, optimism, or faith) were associated with treatment choice/decision-making quality measures. Conclusions . In addition to specialist seen, consulting friends increased men's likelihood of choosing curative treatment. Consulting family or friends increased decision-making difficulty.